A Typology of War Ethics. Issue 3 (2nd October 2017) - Brown, Davis
ABSTRACT: Interdisciplinary communication on war is impeded by doctrinal gaps concerning its morality, immorality, and amorality. Much is written on ad bellum ethical standards for military force by states, mainly in the fields of international politics and religious studies. However, a necessary first step in comparing these different approaches to war ethics with each other is to develop a system for classifying them. The classification system offered in this paper places war ethics on a grid with two scales. One axis of the grid ranges from permissiveness to restrictiveness. The other axis ranges from regard for self to regard for others. Twelve forms of war ethics are assigned points within the grid, including pacifism, just war, holy war, UN Charter obligations, several variants of realism, cost–benefit analysis, isolationism, and various ideological war ethics such as communist and fascist approaches. In doing so, this paper lays the groundwork for "quantifying" war ethics, to enable measurements of their effects against other state-level characteristics and outcomes of interaction.